2019
DOI: 10.2147/jpr.s197967
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bipolar radiofrequency ablation of mandibular branch for refractory V3 trigeminal neuralgia</p>

Abstract: Background: Percutaneous trans-foramen ovale (FO) radiofrequency ablation (RFA) of Gasserian ganglion (GG) is commonly used to treat V3 trigeminal neuralgia (TN). However, this intracranial approach is less selective and safe. Objectives: To report a novel percutaneous within-FO RFA of the V3 under CT-guidance and outcomes with both bipolar and monopolar techniques. Patients and methods: Twenty-six patients with isolated V3 primary TN and FO >6 mm in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Radiofrequency produces a rise in tissue temperature through a high-frequency current that circulates between two electrodes (one placed on the external surface and the other one on the tissue to be treated). This current generates an electric field that causes ionic vibrations, which produce thermal heat that consequently leads to the thermocoagulation of the tissue [ 50 , 54 , 55 ]. The procedure is easy and quick, lasting for about 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency produces a rise in tissue temperature through a high-frequency current that circulates between two electrodes (one placed on the external surface and the other one on the tissue to be treated). This current generates an electric field that causes ionic vibrations, which produce thermal heat that consequently leads to the thermocoagulation of the tissue [ 50 , 54 , 55 ]. The procedure is easy and quick, lasting for about 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…ese findings suggested that with high temperature of Table 3: Numbness degree on day 1 and at 2 y after operation between the two groups (n(%)). [15][16][17]. In this study, high temperature (95°C) was adopted for radiofrequency therapy to reduce thermal attenuation caused by the distance from the radiofrequency target and target nerve, which in turn leads to incomplete nerve destruction and high relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the effect of simple pulsed radiofrequency is not successful, whereas the therapeutic effect of pulsed radiofrequency combined with radiofrequency thermocoagulation is suitable for its clinical use 26,27 . In the comparative study of unipolar and bipolar groups, it was found that the bipolar group exhibited more advantages in pain relief and functional recovery 16,21 . In the clinical treatment of postherpetic neuralgia, the discussion and research of unipolar and bipolar radiofrequency have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the optimal thermal coagulation effect of bipolar more clearly, we explored the radio frequency duration and bipolar distance in the ovalbumin in vitro test 32 . The in vitro ovalbumin model is often used to simulate the internal environment of the human body 21,33 . The results of the ovalbumin in vitro test indicated a difference in the effects of radiofrequency thermocoagulation between the bipolar and unipolar groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation